Structural and acoustical performances of oil palm trunk waste – Elastomeric thermoplastic polyurethane composite - Lubis, Abdul Munir Hidayat Syah; Putra, Azma; Md Yasir, Ahmad Shah Hizam; Irianto, Irianto; Herawan, Safarudin Gazali (Elsevier Ltd, 2024)
In this report, naturally available materials have been utilized in the development of acoustic absorbers. This work presents the study of the effect of oil palm trunks dust (OPTD) loading to the mechanical and acoustical properties of elastomeric thermoplastic polyurethane (TPU). Four composite sheets of 3-mm thickness were prepared by varying the OPTD loadings with 10–40% wt into the polyurethane. Density, modulus elasticity, sound absorption coefficient and sound transmission loss of the samples were measured according to corresponding standards. The OPTD is found to reduce the density of the elastomeric polyurethane and at the same time, it increases the Young's modulus up to 215 MPa. The composite material can be applied as sound absorber panel installed in front of a rigid wall with an air gap. Increasing the air gap, thus lowering the air stiffness, shifts the absorption peak to a lower frequency. With OPTD loadings, the formation of micro-pores in the inner structure helps to improve the peak of sound absorption of the panel at the resonant frequency which can reach above 0.9. As the OPTD loading has effect on density, the effect on the sound transmission loss at the mass-controlled region is also apparent.